2020
DOI: 10.1126/sciimmunol.abd0110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bruton tyrosine kinase in patients with severe COVID-19

Abstract: Patients with severe COVID-19 have a hyperinflammatory immune response suggestive of macrophage activation. Bruton tyrosine kinase (BTK) regulates macrophage signaling and activation. Acalabrutinib, a selective BTK inhibitor, was administered off-label to 19 patients hospitalized with severe COVID-19 (11 on supplemental oxygen; 8 on mechanical ventilation), 18 of whom had increasing oxygen requirements at baseline. Over a 10-14 day treatment course, acalabrutinib improved oxygenation in a majority of patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
358
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(394 citation statements)
references
References 53 publications
(75 reference statements)
16
358
0
10
Order By: Relevance
“…In a recently published letter, Treon et al ( 18 ) reported a beneficial effect of treatment with the Bruton’s tyrosine kinase (BTK) inhibitor ibrutinib on lung inflammation and hypoxia in five patients with Waldenström macroglobulinemia. This lead has been followed by other groups that have reported the potential protective effect of acalabrutinib in patients with lymphoproliferative disorders affected by severe forms of COVID-19 ( 19 ) and by the initiation of clinical trials with BTK inhibitors in patients with severe COVID-19. The mechanisms underlying the activity of BTK inhibitors in improving hypoxia in patients with severe COVID-19 seem to be mediated by an inhibition of exaggerated monocyte autophosphorylation and reduction in interleukin (IL)-6 production.…”
Section: Response To the Coronavirus Disease 2019 Pandemic At The Unimentioning
confidence: 96%
“…In a recently published letter, Treon et al ( 18 ) reported a beneficial effect of treatment with the Bruton’s tyrosine kinase (BTK) inhibitor ibrutinib on lung inflammation and hypoxia in five patients with Waldenström macroglobulinemia. This lead has been followed by other groups that have reported the potential protective effect of acalabrutinib in patients with lymphoproliferative disorders affected by severe forms of COVID-19 ( 19 ) and by the initiation of clinical trials with BTK inhibitors in patients with severe COVID-19. The mechanisms underlying the activity of BTK inhibitors in improving hypoxia in patients with severe COVID-19 seem to be mediated by an inhibition of exaggerated monocyte autophosphorylation and reduction in interleukin (IL)-6 production.…”
Section: Response To the Coronavirus Disease 2019 Pandemic At The Unimentioning
confidence: 96%
“…The concept of a central role of NF-kB pathway in critical stage SARS-CoC-2 infected patients is supported by two recently published studies showing pronounced clinical effect in critical COVID-19 patients by Bruton tyrosine kinase (BTK) inhibitors, correlating with signi cantly decrease in in ammatory parameters (C-reactive protein and IL-6), normalized lymphopenia, and improved oxygenation 40,41 . Bruton tyrosine kinase is known to be involved in TLR7/8-induced TNFa transcription via NF-κB recruitment at the stage of phosphorylation of p65 42 .…”
Section: As a Second Line Of Evidence For The Potential Role Of The Nmentioning
confidence: 96%
“…44 Many other agents that may specifically interfere with thromboinflammatory platelet responses are also of interest, including tyrosine kinase inhibitors that block platelet GPVI signaling (i.e., ibrutinib, acalabrutinib). 39,45,46 Intrinsic and extrinsic coagulation pathways that regulate thrombin formation and promote procoagulant platelet phenotypes are also targets of interest in COVID-19. 41,47 Platelet Phenotype and Function in COVID- 19…”
Section: Platelet Activation and Thrombosis In Covid-19mentioning
confidence: 99%